Open Preperitoneal Mesh Repair of Inguinal Hernia- A Better Approach for the Novice Surgeons (Anwer Khan Modern Medical College Journal, 2023)
Introduction: Inguinal hernia is a common surgical problem in advanced age group, but repair of inguinal hernias after prosthetic mesh repair is usually difficult due to considerable surgical methods, experience and complications. The study is a clinical trial done on patient with any type of inguinal hernia, who were treated by open preperitoneal mesh repair and darning of overlying musculoaponeurotic layers with prolene sutures.Objectives: To study the operating time, hospital stay, postoperative complications and recurrence rate associated with open preperitoneal mesh repair and darning of overlying musculoaponeurotic layers with prolene sutures by novice surgeons.Materials and methods: This observational clinical study in 250 patients having any types of inguinal hernias in new and recurrent cases. The period October 2017 to October 2019 was conducted at department of surgery of Bashundhara Ad-din Medical College Hospital and other private hospitals. The age, gender, operating time, hospital stay, postoperative complications rate and recurrence rate of the patients were evaluated.Results: There were no serious intraoperative complications, there were 230 men and 20 women in the study, whose average age 41.50 (30-72) years. The average operative time taken to complete the surgery and hospital stay were 45.30 (30-120) minutes and 1.5 (1-3) days respectively. Complications include urinary retention in 10%, seroma in 2% and superficial surgical site infection in 2% patients. No recurrence was encountered post-surgery in any of the case till the last follow-up.Conclusions: We concluded that the open preperitoneal mesh repair and darning of overlying musculoaponeurotic layers with prolene sutures is a safe, easier, time consuming and effective methods in a novice surgeon with fewer complications as compared to other conventional open hernia mesh repairs and laparoscopic hernia repairs.AKMMC J 2021; 12(1) : 33-37